(untitled) (Journal of the College of Basic Education, 2022)
Objectives: To know: 1- The physical and psychosocial problems of young patients with anemia. Intermediate (extreme) whiteness. 2- The relationship between physical problems and age. 3- The relationship between psychosocial problems and the patient’s profession. 4- The relationship between psycho-social problems and physical problems. Study methodology